Maize Stem Response to Long-Term Attack by Sesamia nonagrioides - Rodriguez, Victor M.; Padilla, Guillermo; Malvar, Rosa A.; Kallenbach, Mario; Santiago, Rogelio; Butrón, Ana (Frontiers in Plant Science, 2018)
Plants defend themselves against herbivores by activating a plethora of genetic and biochemical mechanisms aimed at reducing plant damage and insect survival. The short-term plant response to insect attack is well understood, but less is known about the maintenance of this response over time. We performed transcriptomic and metabolomics analyses in order to identify genes and metabolites involved in the long-term response of maize to attack by the corn borer Sesamina nonagrioides. To determine the role of elicitors present in caterpillar secretions we also evaluated the response of maize stem challenged with insect regurgitates. The integrative analysis of the omics results revealed that the long-term response in maize is characterized by repression of the primary metabolism and a strong redox response, mainly mediated by germin-like proteins to produce anti-nutritive and toxic compounds that reduce insect viability, and with the glutathione-ascorbate cycle being crucial to minimize the adverse effects of ROS on the plant. Our results suggest that different defense mechanisms are involved in the long-term response compared to those reported during the early response. We also observed a marginal effect of the caterpillar regurgitates on the long-term defensive response.